SSInPIC: um sistema sonoro-interativo auto-organizado - Pereira, Carlos Arthur Avezum (2012)
Computer programming with software such as Pure Data or Max/MSP allows humans to manipulate sonic structures in real-time that can create emergent behavior, increasing the expressive potential of music. This dissertation describes the process and results obtained in the creation and the performance with an Interactive Sound System for Contemporary Improvisation Performances named SSInPIC. The system consists of musical processes with the participation of five agents that interact among themselves: 1) interactive patch (computer application); 2) computer performer; 3) flutist; 4) guitarist; and 5) percussionist The aim was to develop strategies of interaction between these elements based on non-idiomatic improvisation and the concept of self-organization. The concept of self-organization relates to the interactions that occur among the system elements, producing emergent behavior. Thus, the concept of self-organization applied to interactive sound systems is inspired by the openform music experiences found in compositional languages from the mid-twentieth century Western classical music tradition. The issues raised in this research were: which strategies can be used in the idealization of the SSInPIC so that interactions among its elements can produce emergent behavior? Also: which strategies could be used to analyze the emergent behavior in a performance with the SSInPIC? Thus, a five-step working method was established to answer these questions: 1) the study of the concepts related to self-organization and interactive sound systems; 2) the programming of a patch in the Pure Data software environment using probabilistic algorithms to trigger sound samples, and a video monitor to mediate the live electronics process stimulated by the musicians; 3) workshops and performance with the system; 4) the analysis of performances carried out with system; 5) the evaluation of the results. A self-organized behavior of secondary type was observed in the performance with the SSInPIC named Atratores Ou-vistos , which was documented in video. In self-organized behavior of secondary type the face-subject of the system monitors the interactions among the elements with the aim of varying the degree of complexity already designed in the system seen as its potential. The concept of aural models was very important for the establishment of attractors in the interaction between instrumental improvisation and electroacoustic sounds. In addition, concepts related to the study of selforganizing systems and the Mathematical Theory of Information were important tools for analyzing the system behavior. It was concluded that the goal of the research to produce emergent behavior from the self-organization of the elements in the SSInPIC was reached.